The use of geographical analysis in assessing the impact of patients' home addresses on their participation in outpatient cardiac rehabilitation: a prospective cohort study - Atsuko Nakayama; Masatoshi Nagayama; Hiroyuki Morita; Takuya Kawahara; Issei Komuro; Mitsuaki Isobe (Komiyama Printing Co. Ltd, 2020)
Abstract Purpose Geographical analysis is becoming a powerful tool for evaluating the quality of medical services and acquiring fundamental data for medical decision-making. Using geographical analysis, we evaluated the impact of the distance from patients' homes to the hospital on their participation in outpatient cardiac rehabilitation (OCR). Methods All patients hospitalized for percutaneous coronary intervention, coronary artery bypass grafting, valvular surgery, congestive heart failure, and aortic diseases were advised to participate in an OCR program after discharge. Using the dataset of our cohort study of OCR from 2004 to 2015 (n = 9,019), we used geographical analysis to investigate the impact of the distance from patients' homes to hospital on their participation in our OCR program. Results Patients whose road distance from home to hospital was 0-10 km, 10-20 km, and 20-30 km participated more in OCR than those whose road distance was ≧ 30 km (OR 4.34, 95% CI 3.80-4.96; OR 2.98, 95% CI 2.61-3.40; and OR 1.90, 95% CI 1.61-2.23, respectively). Especially in patients with heart failure, the longer the distance, the lesser the participation rate (P < .001). Conclusions Using geographical analysis, we successfully evaluated the factors influencing patients' participation in OCR. This illustrates the importance of using geographical analysis in future epidemiological and clinical studies. Trial registration UMIN000028435.